Multidisciplinary Respiratory Medicine - Sanguinetti, Claudio Maria; Blasi, Francesco
Multidisciplinary Respiratory Medicine is the official journal of the Italian Respiratory Society - Società Italiana di Pneumologia (IRS/SIP). The journal publishes on all aspects of respiratory medicine and related fields, with a particular focus on interdisciplinary and translational research. The interdisciplinary nature of the journal provides a unique opportunity for researchers, clinicians and healthcare professionals across specialties to collaborate and exchange information. The journal provides a high visibility platform for the publication and dissemination of top quality original scientific articles, reviews and important position papers documenting clinical and experimental advances. Given the journal’s interdisciplinary character, the target readership is wider than respiratory medicine, embracing numerous related disciplines (allergology, immunology, internal medicine, geriatrics, infectious diseases, intensive care, etc) and health professionals.